Bacteria Exploit Autophagy for Proteasome Degradation and Enhanced Virulence in Plants. Issue 3 (1st March 2018) - Üstün, Suayib; Hafrén, Anders; Liu, Qinsong; Marshall, Richard S.; Minina, Elena A.; Bozhkov, Peter V.; Vierstra, Richard D.; Hofius, Daniel
Abstract : Pseudomonas syringae activates autophagy in an effector-dependent manner to degrade proteasomes for enhanced pathogenicity, whereas NBR1-dependent autophagic processes counteract disease progression. Abstract: Autophagy and the ubiquitin-proteasome system (UPS) are two major protein degradation pathways implicated in the response to microbial infections in eukaryotes. In animals, the contribution of autophagy and the UPS to antibacterial immunity is well documented and several bacteria have evolved measures to target and exploit these systems to the benefit of infection. In plants, the UPS has been established as a hub for immune responses and is targeted by bacteria to enhance virulence. However, the role of autophagy during plant-bacterial interactions is less understood. Here, we have identified both pro- and antibacterial functions of autophagy mechanisms upon infection of Arabidopsis thaliana with virulent Pseudomonas syringae pv tomato DC3000 ( Pst ). We show that Pst activates autophagy in a type III effector (T3E)-dependent manner and stimulates the autophagic removal of proteasomes (proteaphagy) to support bacterial proliferation. We further identify the T3E Hrp outer protein M1 (HopM1) as a principle mediator of autophagy-inducing activities during infection. In contrast to the probacterial effects of Pst -induced proteaphagy, NEIGHBOR OF BRCA1-dependent selective autophagy counteracts disease progression and limits the formation of HopM1-mediated water-soaked lesions. Together, we demonstrate that distinct autophagy pathways contribute to host immunity and bacterial pathogenesis during Pst infection and provide evidence for an intimate crosstalk between proteasome and autophagy in plant-bacterial interactions.